Analysis of the Use of Filter Screen Rubber Compound Straining process with Multivariate Regression - Yuli Suwarno (Procedia of Engineering and Life Science, 2023)
The rubber compound is processed with a strainer machine to filter out contaminants as a material for making rubber products. The process of filtering the rubber compound with an extrusion-based strainer machine is done with heat to soften and flow the material through the filter screen. This condition will increase the risk of the rubber compound dying (scorching) in the subsequent processing of the rubber compound. The multivariate linear regression model is a regression model with more than one correlated response variable and one or more predictor variables. The purpose of this study was to study the relationship between the use of the same filter screen for the straining process with a certain batch number of straining processes against temperature and time rubber compound scorching. The results showed that the use of filter scree in the straining process and its effect on the characteristics of the rubber compound can be modeled in a multivariate linear regression model following this model [Y ̂_(1) ) Y ̂_((2) ) ]= [78,590+ 3.125X 15.759-1.003X]. The eta square lambda value (η_Δ^2) of 0.925 indicates that the regression model can explain 92.5% of data Based on the multivariate linear regression model, it is possible to calculate the proper replacement period of the filter screen in the rubber compound straining process which increases the efficiency of the rubber compound processing and minimizes the possibility of the rubber compound dying in the process (scorching).